Conventional fixed partial prosthodontics, CADCAM –Zirconio technology and gingival characterization: Case report - Torres Andrade, Dayana (2021)
Fixed prosthodontics is performed in different materials to replace absent dental structures, which can be totally metallic or metallic coated with ceramic, being generally widely used. At present, we have proposals for fixed prostheses with better aesthetic results, such as metal-free prostheses, which allow the professional to reproduce better and in more detail the dental anatomy and in this case also the gingival character. Materials such as zirconia are available that have properties such as biocompatibility, low thermal conductivity, resistance to corrosion, naturalness and aesthetics. In addition, new technological methods are available with which very satisfactory results can be achieved, such as the use of CAD-CAM technology. The present clinical case is focused on the replacement of dental organs and soft tissue, for the rehabilitation of the anterior sector, with materials with favorable characteristics, such as zirconium that contribute to return functionality, phonetics, aesthetics and chewing, through a fixed prosthesis of six metal-free units, with the greatest adaptability to both dental and gingival tissue. The progress of each clinical stage was verified, such as the preparation of the abutments, placement of the provisional, impressions, test of the structure and cementation.